Calculating the Amount of Plastic Waste Based on Type at the Supit Urang Malang Final Processing Site (TPA) - Artiyani, Anis; Warsito, Warsito; Sumitro, Sutiman Bambang; Djati, M. Sasmito; Hidayat, Nur (Postgraduate School of Universitas Brawijaya, 2024)
Waste is one of the crucial environmental problems in Indonesia. Malang City produces around 485 tons of waste every day. This research aims to identify what types of plastic waste are selected at the Supit Urang Final Processing Site and to find out the mass of each type of plastic waste that is sorted, to analyze the volume of plastic waste differentiated based on the types at the Supit Urang Landfill, Malang City. Plastic waste is non-organic waste that is difficult to decompose naturally. In 2019, the Regional Environmental Management Agency (BPLHD) stated that plastic waste in Jakarta reached 13% of 6,000 tons per day and annual calculations reached 5.4 tons. Determining the number of samples in this study used the SNI 19-3964-1994 approach, the waste sampling method, sampling method, and analysis of plastic waste samples were chosen in the research methodology. The research results showed that the types of plastic waste at the Supit Urang landfill include polyethylene terephthalate (PET), low-density polyethylene (LDPE), polypropylene (PP), and others (O), with a mass of each type, namely Polyethylene Terephthalate (PET) 27.7 kg, Low-Density Polyethylene (LDPE) 27.5 kg, Polypropylene (PP) 23.2 kg and Others (O) 21.7 kg. It is hoped that sorting plastic waste according to type through further processing can reduce waste generation in general, especially in Malang City. Keywords: types of plastic waste, sorting at final processing sites, volume of plastic waste